2017
DOI: 10.1093/pcp/pcx026
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously Applied 24-Epibrassinolide (EBL) Ameliorates Detrimental Effects of Salinity by Reducing K+ Efflux via Depolarization-Activated K+ Channels

Abstract: This study has investigated mechanisms conferring beneficial effects of exogenous application of 24-epibrassinolides (EBL) on plant growth and performance under saline conditions. Barley seedlings treated with 0.25 mg l-1 EBL showed significant improvements in root hair length, shoot length, shoot fresh weight and relative water content when grown in the presence of 150 mM NaCl in the growth medium. In addition, EBL treatment significantly decreased the Na+ content in both shoots (by approximately 50%) and roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…First, compared with non-MT-treated Xu 32, MT pretreatment resulted in an evidently enhanced H + efflux that coincided with a decreased K + efflux upon NaCl shock ( Figure 2 ). This pattern of K + /H + flux under NaCl shock has been ascribed to enhanced PM H + –ATPase activity ( Sun et al, 2009b ; Yu et al, 2016 ; Azhar et al, 2017 ). Second, the PM H + –ATPase inhibitor enlarged the salt shock-induced K + efflux in MT-treated Xu 32 root and MCs (Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 98%
“…First, compared with non-MT-treated Xu 32, MT pretreatment resulted in an evidently enhanced H + efflux that coincided with a decreased K + efflux upon NaCl shock ( Figure 2 ). This pattern of K + /H + flux under NaCl shock has been ascribed to enhanced PM H + –ATPase activity ( Sun et al, 2009b ; Yu et al, 2016 ; Azhar et al, 2017 ). Second, the PM H + –ATPase inhibitor enlarged the salt shock-induced K + efflux in MT-treated Xu 32 root and MCs (Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 98%
“…Given that exogenous BL was applied to the leaves, we inferred that the increased K + content in roots was caused by the transportation and distribution of K + between shoots and roots, which was affected by exogenous BL to the leaves. Recently, Azhar et al (2017) showed that BL in the growth medium prevented salt-induced K + leak from shoots and roots. They also noted that BL decreased K + efflux under salt stress by controlling depolarization-activated GORK channels.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of osmolytes, such as sorbitol, proline, and lycine, is critical to osmotic balance (Shahid et al, 2014;Yusuf et al, 2017). Maintaining homeostasis of Na + and K + in cells by activating Na + and K + transporters is vital for plant salt stress tolerance (Azhar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The exogenous application of 24-epibrassinolide (EBR) can be a possible solution to mitigate the damage caused by deficiencies and excess Zn in plants because EBR is one of the most bioactive forms of brassinosteroids (BRs); it is extracted from plants and is biodegradable (Azhar et al 2017). This steroid presents a broad spectrum of systemic action on plant metabolism (Oh et al 2012), including CO 2 (Li et al 2016b), gas exchange (Swamy and Rao 2009), photochemical efficiency (Thussagunpanit et al 2015), antioxidant metabolism (Xia et al 2009) and growth rate (Abdullahi et al 2003).…”
Section: Introductionmentioning
confidence: 99%